The role of tissue factor and autophagy in pulmonary vascular remodeling in a rat model for chronic thromboembolic pulmonary hypertension. Issue 1 (December 2016) - Deng, Chaosheng; Wu, Dawen; Yang, Minxia; Chen, Yunfei; Ding, Haibo; Zhong, Zhanghua; Lian, Ningfang; Zhang, Qiaoxian; Wu, Shuang; Liu, Kaixiong
Abstract Background Few reports have examined tissue factor (TF) and autophagy expression in chronic pulmonary thromboembolic hypertension (CTEPH) animal models.Objectives : To investigate the role of tissue factor (TF), autophagy and their interactions during chronic thromboembolic pulmonary hypertension (CTEPH) pathogenesis in a rat model. Methods Autologous blood clots were repeatedly injected into the left jugular vein of rats with injecting endogenous fibrinolysis inhibitor tranexamic acid (TXA). Mean pulmonary arterial pressure (mPAP), histopathology and TF, Beclin-1 and microtubule-associated protein 1 light chain (LC3) expression levels were detected. Results The mPAP and vessel wall area/total area (WA/TA) ratio in the experiment group increased significantly (P  < 0.05). TF mRNA and protein expression levels in the experiment group increased significantly (P  < 0.05). Beclin-1 and LC3B mRNA and protein expression levels were lower in the experiment group (P  < 0.05). The mPAP had a positive correlation with WA/TA ratio (r  = 0.955, P  < 0.05). Beclin-1 and LC3B protein expression had a negative correlation with the WA/TA ratio (r  = -0.963, P  < 0.05, r  = -0.965, P  < 0.05, respectively). TF protein expression had a negative correlation with both Beclin-1 and LC3B protein expression (r  = -0.995, P < 0.05, r  = -0972, P <  0.05, respectively). Conclusions A rat model of CTEPH can be established by repeatedly introducing autologous blood clots into the pulmonary artery with injecting TXA. TF and autophagy may play a key role during CTEPH pathogenesis, especially in vascular remodeling.